Motor and cognitive function after unipolar depressive episodes: a 6 years longitudinal observational study - Straub, Stephanie; Hobert, Markus A.; Emmert, Kirsten; Hansen, Clint; Elshehabi, Morad; Suenkel, Ulrike; Wurster, Isabel; Roeben, Benjamin; Zimmermann, Milan; Fallgatter, Andreas J.; Berg, Daniela; Maetzler, Walter (Frontiers in Psychology, 2025)
IntroductionUnipolar depression is a frequent psychiatric disorder and associated with cognitive and motor deficits. It is also a prodromal or risk marker for various neurodegenerative diseases. Little research has been done on the extent to which motor and cognitive deficits persist in remitted depressive episode, and to what extent these deficits can be progressive.MethodsA total of 401 healthy subjects of the Tübingen TREND study aged between 50 and 80 years were examined over 6 years at intervals of 2 years. Of those, 81 had a positive history of unipolar depression (Dep+) and 320 had not (Dep-). We ruled out currently depressive participants. Mini-Mental-State Examination (MMSE), Consortium to Establish a Registry for Alzheimer’s disease (CERAD), the motor part of the Movement disorder society-revised version of the Unified Parkinson disease rating scale (MDS-UPDRS III), gait speed, and dual tasking parameters were compared between groups.ResultsDep+ had lower gait velocity than Dep-. No significant change in parameters was found over the observed time.DiscussionReduced gait speed in Dep+ may have potential as a diagnostic and prognostic marker for Dep- if confirmed in further studies. The lack of progression of all studied parameters over 6 years specifically in Dep+ argues against a relevant potential of this approach to define prodromal neurodegenerative cohorts by history of depression.